Enhanced Cell Growth and Astaxanthin Production in Haematococcus lacustris by Mechanostimulation of Seed Cysts - Catherine Christabel; Bolam Kim; Aditya Lakshmi Narasimhan; Laxmi Priya Sathiyavahisan; Dea Prianka Ayu Ilhamsyah; Eui-Jin Kim; You-Kwan Oh (Applied Sciences)
The slow growth and complex life cycle of Haematococcus lacustris pose significant challenges for cost-effective astaxanthin production. This study explores the use of microfluidic collision treatment to stimulate the germination of dormant seed cysts, thereby improving photosynthetic cell growth and astaxanthin productivity in H. lacustris cultivated in well plate and flask cultures. The flow rate (1.0–3.0 mL/min) and the number of T-junction loops (3–30) were optimized in the microfluidic device. Under optimal conditions (a flow rate of 2.0 mL/min with 10 loops), the total cell number density in well plate cultures increased by 44.5% compared to untreated controls, reaching 28.9 ± 2.0 × 104 cells/mL after 72 h. In flask cultures, treated cysts showed a 21% increase in astaxanthin productivity after 30 d, reaching 0.95 mg/L/d, due to higher biomass concentrations, while the astaxanthin content per cell remained constant. However, excessive physical collision stress at higher flow rates and loop numbers resulted in reduced cell viability and cell damage. These findings suggest that carefully controlled cyst mechanostimulation can be an effective and environmentally friendly strategy for Haematococcus biorefining, enabling the production of multiple bioactive products.